2022
DOI: 10.3390/cancers14235764
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis and Its Role in Cervical Cancer

Abstract: Pyroptosis, an inflammatory programmed cell death, is characterized by the caspase-mediated pore formation of plasma membranes and the release of large quantities of inflammatory mediators. In recent years, the morphological characteristics, induction mechanism and action process of pyroptosis have been gradually unraveled. As a malignant tumor with high morbidity and mortality, cervical cancer is seriously harmful to women's health. It has been found that pyroptosis is closely related to the initiation and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…In contrast, similar to apoptotic cells, necroptotic cells may exhibit PS on the outer membrane. Furthermore, as discussed earlier, TNF is the most well-known cytokine triggering the necroptosis pathway [ 67 , 68 , 69 ]. The above-mentioned findings suggest that the cell death observed following treatment with MM -compounds may be a combination of both apoptosis and necroptosis, depending on the cell type, incubation time, and compound concentration ( Figure 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, similar to apoptotic cells, necroptotic cells may exhibit PS on the outer membrane. Furthermore, as discussed earlier, TNF is the most well-known cytokine triggering the necroptosis pathway [ 67 , 68 , 69 ]. The above-mentioned findings suggest that the cell death observed following treatment with MM -compounds may be a combination of both apoptosis and necroptosis, depending on the cell type, incubation time, and compound concentration ( Figure 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated SIRT1 expression inhibits the AIM2 inflammasome, a mechanism that suppresses pyroptosis while promoting the proliferation of cancer cells. Providing EVs with AIM2 inflammasome proteins was found to induce pyroptosis in cancer cells by downregulating SIRT1 [ 121 , 122 ]. Necroptosis acts as an alternative form of programmed cell death that surpasses resistance to apoptosis, and has the potential to initiate and enhance immune responses against tumors in cancer treatment.…”
Section: Evs As Integrators Of Homeostasismentioning
confidence: 99%
“…Moreover, pyroptosis activation by inhibiting SF3B1 improves the development of ovarian cancer 13 . Additionally, recent research has shown pyroptosis is directly associated with the beginning and development of CC 14 . Therefore, it is worth figuring out more novel molecules involved in pyroptotic pathways linked to CC.…”
Section: Introductionmentioning
confidence: 99%